A novel combination of Soluplus® and Poloxamer for Meloxicam solid dispersions via hot melt extrusion for rapid onset of action—part 1: dissolution and stability studies - Maha F. Emam, Nesrin F. Taha, Laila H. Emara (Journal of Applied Pharmaceutical Science, 2021)
The hot melt extrusion (HME) technique was proposed to prepare solid dispersions (SDs) of the high melting point meloxicam (MLX) for the first time. Extruded MLX/SDs (EXT) prepared by HME were compared with fusion (FUS) and physical mixture (PM) using different ratios of Soluplus® (SOL) to Poloxamer (POLOX), with MLX kept constant at 2.50% (w/w). Accelerated and bench stability studies were conducted for 6 and 12 months, respectively. MLX/SDs were evaluated by in vitro dissolution tests, drug content, differential scanning calorimetry (DSC), and polarized light microscope (PLM). The existence of MLX in an amorphous state in EXT samples was observed by DSC/PLM. All batches improved dissolution in contrast to pure MLX, with the highest dissolution rate observed for EXT samples at different carriers’ ratios. In the SOL–POLOX ratio of 2.3:1.0, the EXT samples showed about 20.7-, 1.9-, and 1.7-folds increases in dissolution compared to plain drug, PM, and FUS, respectively. Most of the stored samples maintained their stability and successfully inhibit MLX recrystallization after 12 months of bench storage, as well as 6 months at 40°C/75% RH. However, EXT samples with a high ratio of SOL stored at 40°C/75% RH for 6 months showed gradual MLX recrystallization and a significant decrease in dissolution. The HME provided a continuous, solvent-free, ecofriendly manufacturing process for the successful production of MLX/SDs. A novel combination of SOL and POLOX proved their efficiency in facilitating the extrusion of SDs at a lower temperature for the first time in the literature.
Keywords: Enhanced dissolution, hot-melt extrusion, Soluplus®, Poloxamer, meloxicam, accelerated and bench stability.